Anthropocene Antarctica: Approaches, issues and debates - Leane, E; McGee, JA (Routledge, 2020)
This chapter outlines key debates about the Anthropocene, identifying the distinctive issues that the concept raises in relation to the Antarctic region. The chapter establishes the centrality of Antarctica to Earths future, as a source of scientific data (such as that derived from ice cores); as an endangered environment (from ice melt, marine microplastic pollution, ocean acidification and other changes); and as a planetary-scale threat (through sea-level rise). The Anthropocene, in turn, changes the way humans think about Antarctica, challenging stereotypes of an untouched wilderness. Long conceived as a natural laboratory to be occupied and known primarily by scientists, the South Polar region has in the Anthropocene become an ironically productive place from which to explore human relationships with the nonhuman world. As a result, Antarctica is increasingly attracting attention from researchers within the humanities, law and social sciences. The chapter provides an overview of key Antarctic-related research emerging from these fields, and contextualizes the contributions to this collection within this growing body of thought.